Prediction and Estimation of Postoperative Refractive Error in Phacoemulsification: Using Ultrasound A-Scan and Intra Ocular Lens Master - Bhatta, Sabitri; Narayan Joshi, Sagun; Thapa, Madhu; Awasthi, Suresh; Shankar Shrestha, Gauri; Dev Joshi, Niraj (Journal of Nepal Health Research Council, 2024)
Background: This study aims to predict and estimate the postoperative refractive outcome in participants undergoing phacoemulsification using IOL Master and A-scan biometry.Methods: A cross-sectional study was done where ninety eyes of 90 participants undergone phacoemulsification using SRK/T formula were included in longitudinal research. Each participant underwent axial length (AL) measurement by IOL Master and A-scan, and keratometry reading (k- reading) by manual TOPCON keratometer and automated keratometer on IOL master for IOL power calculation. All the pre-operative measurements between A-scan and IOL master and two keratometers were compared using paired-t tests. The four-week postoperative refractive error was estimated using univariate analysis and its prediction was compared with the ocular biometry parameters using quadratic regression.Results: Preoperative findings were higher for AL and ACD by IOL master and A-scan (0.27±0.14mm; p<0.001, 0.14±0.31mm, p<0.001) respectively. The AL and K-reading were found to be strong predictors of IOL power calculation (β = -1.07; p<0.001, β = 0.75; p<0.001), respectively. The AL, K-reading were found to be strong predictors for four-week postoperative refractive error (β = -1.563; p = 0.012, β = 1.052; p = 0.012) where postoperative error was found to be higher (F = 7.521, p<0.001) in A-scan than IOL Master. For K-reading, the two keratometer’s and for AL by A-scan and IOL Master’s level of agreement (95% LoA) was comparable (-0.15 to 0.12mm and -0.01 to 0.54mm). Conclusions: IOL Master is more reliable for ocular biometry and minimizes postoperative refractive error.Keywords: Axial length; intraocular lens power; keratometry-reading; refractive error estimation; postoperative refractive error.